Over a million students use our free study notes to help them with their homework
First multiply the second equation by 2, so it becomes 2x + 12y = -8. Then subtract the second equation from the first one which gives (2x - 2x) + (-5y - 12y) = (9 - -8), -17y = 17. Therefore y = -1. Plug...
This question can be approached using the Pythagoras Theorem, with the line connecting these 2 points being the hypotenuse (longest side of the triangle). Side lengths:1) 7-3=4 2) 9-2=7Therefore, the dist...
Draw the triangle - recognising that it is a right angled trianglefind the scale factoruse the formula: 0.5 x base x height = area To find the scale factor you must divide the total perimeter by the sum o...
Primarily, we should attempt to make either the x or y values of either equation be the same value, or the equivalent negative value. This is so we can add or subtract the equations to leave us with one v...
We can differentiate the expression using the quotient rule. If f(x)=u(x)/v(x) then f'(x)=(u'(x)v(x)-u(x)v'(x))/v(x)^2. In this case u(x)=3x^2-5x so u'(x)=6x-5 and v(x)=4x^3+2x^2 so v'(x)= 12x^2+4...
←
418
419
420
421
422
→
Internet Safety
Payment Security
Cyber
Essentials